Sex differences in central benzodiazepine receptor densities and circulating corticosterone release after acute stress in broiler chicks - Marin, Raul Hector (2002)
The purpose of the study was to determine the effect of sex on central benzodiazepine receptor (CBR) and serum corticosterone (CS) responses to an acute stressor in broiler chicks. Birds were housed in ten mixed-sex groups of eight chicks per cage. At 15 d of age, chicks were taken from a randomly selected cage and blood was immediately sampled (undisturbed controls), or they were taken from the same cage and immersed up to their necks in warm water (partial water immersion, PWI) for 15 min before blood was sampled. After blood sampling, forebrains were dissected for preparation of membranes, and bird sex was determined by gonadal inspection. Serum CS levels were determined by a competitive protein-binding assay. CBR densities were determined by radiolabeled receptor binding assay. There were no sex differences in serum CS levels or benzodiazepine receptor densities in controls. Exposure to PWI significantly increased (P < 0.01) circulating CS levels in both sexes, and this elevation was more pronounced (P < 0.01) in males than in females. Male, but not female, chicks also showed a significant stressor-induced increase (P < 0.01) in CBR densities. These findings showed sexual differences in acute, stressor-induced benzodiazepine and adrenocortical responses that suggest broiler males are more stress-susceptible than females.